Application of Islamic Accounting and Benefits in Rahn Tasjily Financing in the Management of Islamic Multipurpose Cooperatives - Kayla Zahara Putri Nasada; Hendra Harmain; Nur Ahmadi Bi Rahmani (Faculty of Islamic Business and Management, 2025)
Non-bank financial institutions are very often challenged to implement Islamic financing, especially in the standard of financial records. The purpose of this research is to evaluate the implementation of the rahn tasjily financing system, the application of sharia accounting to rahn tasjily, compliance with the DSN MUI fatwa related to rahn tasjily, compliance with Qanun on Islamic financial institutions, and the benefits of financing for members and employees at the Wangi Sari Selamat Jaya Sharia Multipurpose Cooperative (WASSALAM) Aceh Tamiang. The novelty of the research lies in the Qanun as the standard of Islamic financial institutions in Aceh. Although previous research has researched how accounting is applied to rahn tasjily, but there are still few who discuss its compatibility with the Qanun LKS This research uses a descriptive-qualitative approach with the Participatory Action Research (PAR) method, through in-depth interviews with participants. The research findings show that Wassalam Cooperative has implemented sharia-compliant financing, but is still unable to provide debt with uniform ujrah because each customer has different terms and conditions that must be met. Some aspects of this financing are also in accordance with PSAK 107, but the lack of staff understanding of accounting standards, especially PSAK 107, causes the presentation and disclosure aspects of financing to not be implemented properly. The cooperative is committed to the fatwa of DSN MUI and Aceh Qanun No. 11/2018, to ensure compliance with sharia regulations. The cooperative channelled the benefits of interest-free financing in accordance with sharia principles to empower the community's economy while enhancing sharia financial education. This implementation also encourages cooperatives as Islamic financial institutions to continue learning to minimise the risk of accounting errors and optimise financial performance. Theoretically, this research enriches the Islamic accounting and sustainable finance literature and contributes to evaluating regulations related to rahn tasjily.